Transduodenal resection of a choledochocele (type III choledochal cyst) with sphincteroplasty: A case report - Inna N. Lobeck; Phylicia Dupree; Richard A. Falcone Jr; Tom K. Lin; Andrew T. Trout; Jaimie D. Nathan; Greg M. Tiao (Elsevier, 2016)
Choledochal cysts are rare congenital anomalies of the biliary tree which may progress to obstruction or malignancy. Of the five Todani variants, choledochocele, or type III choledochal cyst is the rarest. In this case report, we describe a previously healthy 10-year old female who presented with a choledochocele and was treated by near-total excision with transposition of the common channel, resulting in an extended sphincteroplasty.